Adopsi Cobit 2019 Untuk Mengukur Tingkat Kematangan Tata Kelola Teknologi Informasi Pada Dinas Kependudukan Dan Pencatatan Sipil - Ridho Adilaksana; Muhamad Ariandi; Fitri Purwaningtias; Maria Ulfa (LPPM STIKOM Tunas Bangsa, 2024)
Information Technology Governance (IT Governance) is an important concept in managing information technology infrastructure in organizations, including the Department of Population and Civil Registration (DISDUKCAPIL). This research aims to measure the maturity level of information technology governance at DUKCAPIL using the COBIT 2019 framework with a focus on the APO12 (Risk Management), APO13 (Security Management), and BAI10 (Configuration Management) domains at the capability level. This research method involves a case study at the Department of Population and Civil Registration (DISDUKCAPIL), where data is collected through interviews with information technology staff, analysis of policy and procedure documents, as well as direct observation of the existing information technology environment. The data is then analyzed by referring to the COBIT 2019 framework, especially the APO12, APO13 and BAI10 domains by considering the level of capability measured using the COBIT scale, the objects to be evaluated are APO12 – Managed Risk, APO13 – Managed Security and BAI1 0– managed Configuration evaluates with capability level. Capability level objectives can be increased by carrying out activities that have not been carried out by DISDUKCAPIL until they reach the full value for each level.